Description of the new solifuge Gylippus (Paragylippus) hakkaricus sp. n. (Gylippidae, Solifugae) - Erdek, Melek (Zootaxa, 2019)
A new solifuge species of Gylippinae Roewer 1933, Gylippus (Paragylippus) hakkaricus sp. n., is described and illustrated on the basis of both sexes from Hakkari Province, Southeast Turkey. The flagellum, flagellar setal complex, pedipalp in male and genital operculum in female are discussed and compared with related Gylippus (Paragylippus) species.